In vitro fertilization and embryo transfer. Experience of an assisted reproductive technology program at 3330 meters above sea level - Vargas Tominaga, Luis (2015)
Objective: To determine the success rates of in vitro fertilization (IVF) in an assisted reproductive technology program at 3 330 meters above sea level. Design: Descriptive, retrospective study. Setting: Centro de Fertilidad y Ginecologia del Sur, Cusco, Peru, city at 3 330 meters (10 989 feet) above sea level. Participants: Couples with infertility diagnosis and indication of IVF. Interventions: We performed IVF and embryo transfer in 27 couples. Main outcome measures: Implantation, biochemical pregnancy, and clinical pregnancy rates. Results: Implantation rate was 14,3%, biochemical pregnancy rate 37,0% and clinical pregnancy rate 22,2%. Conclusions: IVF cycles at 3 330 meters above sea level seem to achieve implantation and clinical pregnancy rates similar to national and international reports.